High-dose vitamin D3 in the treatment of severe acute malnutrition: a multicenter double-blind randomized controlled trial. Issue 5 (2nd May 2018) - Saleem, Javeria; Zakar, Rubeena; Zakar, Muhammad Z; Belay, Mulugeta; Rowe, Marion; Timms, Peter M; Scragg, Robert; Martineau, Adrian R
ABSTRACT: Background: Vitamin D deficiency is common in children with severe acute malnutrition, in whom it is associated with severe wasting. Ready-to-use therapeutic food (the standard treatment) contains modest amounts of vitamin D that do not reliably correct deficiency. Objective: The aim of this study was to determine whether high-dose oral vitamin D3 enhances weight gain and development in children with uncomplicated severe acute malnutrition. Design: We conducted a randomized placebo-controlled trial of high-dose vitamin D3 supplementation in children aged 6–58 mo with uncomplicated severe acute malnutrition in Pakistan. Participants were randomly assigned to receive 2 oral doses of 200, 000 IU vitamin D3 or placebo at 2 and 4 wk after starting ready-to-use therapeutic food. The primary outcome was the proportion of participants gaining >15% of baseline weight at 8 wk after starting ready-to-use therapeutic food (the end of the study). Secondary outcomes were mean weight-for-height or -length z score and the proportion of participants with delayed development at the end of the study (assessed with the Denver Development Screening Tool II), adjusted for baseline values. Results: Of the 194 randomly assigned children who started the study, 185 completed the follow-up and were included in the analysis (93 assigned to intervention, 92 to control). High-dose vitamin D3 did not influence the proportion of children gaining >15% of baseline weight at the end of the study (RR: 1.04; 95% CI: 0.94, 1.15, P = 0.47), but it did increase the weight-for-height or -length z score (adjusted mean difference: 1.07; 95% CI: 0.49, 1.65, P < 0.001) and reduce the proportion of participants with delayed global development [adjusted RR (aRR): 0.49; 95% CI: 0.31, 0.77, P = 0.002], delayed gross motor development (aRR: 0.29; 95% CI: 0.13, 0.64, P = 0.002), delayed fine motor development (aRR: 0.59; 95% CI: 0.38, 0.91, P = 0.018), and delayed language development (aRR: 0.57; 95% CI: 0.34, 0.96, P = 0.036). Conclusions: High-dose vitamin D3 improved the mean weight-for-height or -length z score and developmental indexes in children receiving standard therapy for uncomplicated severe acute malnutrition in Pakistan. This trial was registered at clinicaltrials.gov as NCT03170479.